PENGARUH SIHIR TERHADAP AKIDAH MUSLIM DALAM TAFSIR AL-MISHBAH KARYA MUHAMMAD QURAISH SIHAB - Farhan, M. (Fakultas Agama Islam, 2023)
This research discusses the concept of magic, the interpretation of Al-Qur'an verses about magic, and its influence on a Muslim's faith according to the interpretation of Al-Misbah. This research is qualitative research in the form of literature research. The results of the research show that the concept of magic in Islam is based on the context of the Al-Qur'an as a strange or miraculous (occult) act that is unknown according to custom beyond human expectations. Magic shows amazing or extraordinary things, but it is not like a miracle, nor is it sacred. Magic can be done through words, actions, amulets, oaths and other things shown by the sorcerer. Analysis of the interpretation of Al-Quran verses about magic in a Muslim's faith in Surah Al-Baqarah verse 102, Yusuf verses 77, 81 and 82, and Thaha verses 67 and 69 interpret that magic as in the time of Prophet Sulaiman and Prophet Isa is deception. and the deeds of Satan. According to Al-Misbah's interpretation, the influence of magic on Muslim faith is an act of shirk, namely an act that involves forces other than the power of Allah SWT. According to Quraish Shihab in his interpretation of Al-Misbah in several letters and verses, believing in magic and committing acts of magic are acts of shirk that can damage a person's faith.